THE DIFFERENCES OF STUDENTS’ LEARNING MOTIVATION IN LEARNING CIVIC EDUCATION USING DEMOCRATIC LEARNING MODEL AND CONVENTIONAL LEARNING MODEL IN GRADE V OF SD BERTINGKAT KELAPA LIMA 3, KUPANG - Nahak, Roswita Lioba (PEOPLE: International Journal of Social Sciences, 2017)
The aims of this study are: (1) to describe the difference between learning achievements of students studying civic education using conventional learning model and democratic keywords learning model; (2) to describe the difference of students learning achievement Civic education among high and fair learning motivation, students with fair learning achievement to low learning achievement and students with high learning achievement to low learning achievement; (3) to determine whether there is an interaction between the democratic learning model and learning motivation towards grade V students’ Civic education learning achievement. This study uses a quasi-experimental method, which has population 40 students of grade V of SD Bertingkat Kelapa Lima 3 Kupang. Sampling used was judgment sampling technique which uses all population as sample. The data collection technique for students’ achievement of Civic education used test and students’ learning motivation used questionnaire. The data analysis technique used was ANOVA then the final data was computed by using Schaffe method. The results (1) are the differences in learning achievement between students learning Civic education using conventional learning models with students who learn using model democratic techniques keywords (Keyword). This is proved by the FA = 13.047> F table = 4.13; (2) there are differences in learning achievement Civic education between students with high, fair and low learning motivation. This is proved by the FB = 20.703> F table = 3.28; (3) there is no interaction between the learning model of democratic and students’ motivation towards learning achievement of grade 5 students Civic education. This is proved by FAB=0,184 < FCritic=3,28.